The essence of being connected: the lived experience of mothers with young children in newer residential areas - Strange, C.; Fisher, C.; Howat, Peter; Wood, L. (Routledge, 2014)
Parenthood is a significant life transition and a time of increased social support need. In newer residential areas, a lag in social infrastructure and family relocation can influence potential isolation of families with young children. This qualitative study explored the lived experiences of being connected to local communities for mothers with children aged 0–5 years. Family insights were obtained through in-depth interviews with 12 mothers who were primary caregivers, homeowners and living in newer residential areas in outer suburban Perth, Western Australia. For mothers with young children, being connected to the local community appears to be shaped from their past and present lived experience as well as future aspirations. Connectedness evolves and may develop more slowly in newer communities where social relationships and networks are often recently formed. ‘Interaction’, ‘knowing what's going on’ and ‘help is nearby if you need it’ were identified as the essential themes of connectedness for mothers and families in this study. Belonging was identified as an incidental theme as not all mothers who felt connected felt like they belonged. The findings provide insight for professionals and agencies working with families with young children as well as planners of newer residential areas.